Pengembangan Model Edukasi Partisipatif Berbasis Evidence-Based Practice dalam Penerapan PHBS di Pondok Pesantren - Handayani, Sri; Sirait , Reni Aprinawaty; Susanti, Dewi (Journal of Pharmaceutical and Sciences, 2025)
Clean and Healthy Living Behavior (CHLB) is a crucial preventive measure to improve health status in Islamic boarding schools (pesantren). This study aimed to develop an evidence-based education model for CHLB in a pesantren in West Sumatra. The research applied a Research and Development (R&D) design through the stages of analysis, design, development, implementation, and evaluation. Data were collected through observation, in-depth interviews, and pre- and post-test questionnaires. The findings revealed that unhealthy behaviors among students remained high, with 93.47% not practicing handwashing with soap, 50% littering, 65.22% spitting in public areas, and 76.08% not engaging in mosquito larvae control. Interviews with caregivers and administrators indicated the absence of nutritionists in meal planning, lack of educational media, and limited health education, which was only provided once during the Covid-19 pandemic. The developed educational model proved effective, demonstrated by significant improvements in knowledge (increase of 43 points) and attitudes (increase of 25 points) after the intervention. Respondents considered the model practical, easy to understand, and culturally appropriate within the pesantren context. Therefore, the participatory, evidence-based education model is feasible to be implemented more widely to strengthen CHLB practices and prevent behavior-related diseases in Islamic boarding schools.